Effectiveness of Cognitive-Analytic Therapy on Improving Personality Organization, Worry, and Experiential Avoidance in Adolescents with Borderline Personality Disorder - Dehghan, Maryam; Mirzaei, Masoumeh; Rezaei, Mina; Didehjahan, Najla; Pourmohammad Ghouchani, Kamran (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective:  The present study aimed to examine the effectiveness of cognitive-analytic therapy (CAT) in improving personality organization, reducing worry, and decreasing experiential avoidance among adolescents diagnosed with borderline personality disorder (BPD).Methods and Materials: This quasi-experimental study employed a pretest–posttest control group design. The statistical population included all adolescents with BPD referred to counseling and social work centers in Tehran in 2025. Thirty participants were selected through purposive sampling and randomly assigned to experimental (n = 15) and control (n = 15) groups. The experimental group received eight sessions of group CAT (90 minutes each, twice per week), while the control group was placed on a waiting list for two months. Data collection tools included the Inventory of Personality Organization (IPO), the Penn State Worry Questionnaire (PSWQ), and the Acceptance and Action Questionnaire–II (AAQ-II). Data were analyzed using multivariate analysis of covariance (MANCOVA) in SPSS-26.Findings: The results demonstrated that, after controlling for pretest effects, there were statistically significant differences between the experimental and control groups in the posttest scores of personality organization (F = 333.19, p < .049, η² = .51), worry (F = 169.93, p < .006, η² = .55), and experiential avoidance (F = 287.14, p < .007, η² = .57). These findings indicate that CAT significantly improved personality organization while reducing worry and experiential avoidance in adolescents with BPD.Conclusion: The therapy enhances self-awareness, reduces maladaptive avoidance strategies, and improves overall personality functioning, making it a promising option for clinical practice with this population.